Treatment of cervical cancer metastatic to the abdominal wall with reconstruction using a composite myocutaneous flap: A case report - Dalia Khalife; Alaa El Housheimi; Ali Khalil; Salim C. Saba; Muhieddine Seoud; Rayan Rammal; Ibrahim Elias Abdallah; Reem Abdallah (Elsevier, 2019)
A 43-year-old woman treated with radical hysterectomy 1 year ago for cervical cancer presented with a suprapubic abdominal mass. A 15 cm necrotic mass from the abdominal wall along with 2 small bowel loops and the dome of the bladder were resected. The peritoneal defect was reconstructed with a pedicled anterolateral thigh and Vastus Lateralis muscle composite flap. Pathology showed invasive non-keratinizing moderately differentiated squamous cell carcinoma, consistent with metastatic cervical cancer, involving urinary bladder, bowel and soft tissue. With advancement in reconstructive surgery, extensive resection with defect closure in properly selected cases of metastatic cervical cancer to the abdominal wall may be considered in an attempt at improving quality of life and overall survival. Keywords: Abdominal wall lesion, Cervical cancer, Metastasis of cervical cancer, Resection of lesion